Expectations and the Stability of Stock-Flow Consistent Models - Huub Meijers; Joan Muysken; Giulia Piccillo (Center for Economic Studies and ifo Institute (CESifo), 2023)
Expectations are usually introduced in macroeconomic stock-flow consistent models (SFC-models from hereon) in an ad hoc way, without much motivation. Moreover, these are usually very simple forms of expectations, and certainly not some form of rational expectations. The implicit assumption is that expectations do not matter very much in these models. In this paper, we argue that expectations are very important in understanding the way the economy reacts to a shock, since the stability of the economy is dependent on the nature of expectations. We show for instance that for simple expectations, the more backward-looking they are, the more stable the economy tends to become, whereas the opposite is true for enhanced expectations. For that purpose, we use a simple model, based on the models in Godley & Lavoie, 2007. The model includes next to households, firms and government, a financial sector and a foreign sector. First, we analyse the stationary state solution and analyse its properties. We show that this model is only stable when either the tax rate or government debt is not too high. We also point out the self-fulfilling properties of optimism and pessimism in expectations in this model. Next, we show that under "perfect foresight" the model becomes saddle point stable – strong restrictions on taxes and government debt are necessary to guarantee the stability of the model. Under simple naïve expectations the model becomes more stable compared to the stationary state. However, it becomes less stable when naïve expectations are enhanced by the impact of growth. Finally, we show how under fundamentalist and adaptive expectations the stability of the model is affected in an intermediate way. Second, we analyse the adaption process after a shock. Here we find that GDP adjusts very slowly under naïve expectations and faster under stationary and fundamentalist expectations. All in all, we conclude that expectations do matter: the kind of expectations introduced in an SFC model strongly influence both its stability properties and the speed of adjustment to shocks. In our simple model, fundamentalist expectations turn out to have the best combination of stability and speed of adjustment.
Keywords: E70; B50; E60; F45; F47; 330; expectations; financialisation; wealth accumulation; stock-flow consistent modelling